2009
DOI: 10.1007/s00024-009-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Monte Carlo Method Based Artificial Neural Networks Approach for Rock Boundaries Identification: A Case Study from the KTB Bore Hole

Abstract: Identification of rock boundaries and structural features from well log response is a fundamental problem in geological field studies. However, in a complex geologic situation, such as in the presence of crystalline rocks where metamorphisms lead to facies changes, it is not easy to discern accurate information from well log data using conventional artificial neural network (ANN) methods. Moreover inferences drawn by such methods are also found to be ambiguous because of the strong overlapping of well log sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…There are, however, several limitations in conventional neural network approaches also (Bishop, 1995;Maiti and Tiwari, 2009). One of the major limitations is that the network is trained by maximizing a likelihood function of the parameters or equivalently minimizing an error function in order to obtain the best set of parameters starting with an initial random set of parameters.…”
Section: S Maiti Et Al: Inversion Of DC Resistivity Data Of Koyna Rmentioning
confidence: 99%
“…There are, however, several limitations in conventional neural network approaches also (Bishop, 1995;Maiti and Tiwari, 2009). One of the major limitations is that the network is trained by maximizing a likelihood function of the parameters or equivalently minimizing an error function in order to obtain the best set of parameters starting with an initial random set of parameters.…”
Section: S Maiti Et Al: Inversion Of DC Resistivity Data Of Koyna Rmentioning
confidence: 99%
“…These occur in a range of continental and oceanic settings, where a number of boreholes have been and continued to be drilled in order to provide information of the Earth's crust by means of geophysical surveys and geological mapping (Harvey et al, 2005). Several studies have been reported by geophysicists based on crystalline rocks using well logging data (see for example Pratsone et al, 1992;Pechnig et al,1997Pechnig et al, , 2005Bartetzko et al, 2005;Maiti and Tiwari, 2009;Luo and Pan, 2010;. The general understanding collected from these studies show that, the well logging data from crystalline rocks are not simple to analyze because of their complicated geological characteristics and the difficulty in understanding and using the intensive information content in these data.…”
Section: Introductionmentioning
confidence: 96%
“…For example: (1) for seismic event classification (Dystart and Pulli, 1990), (2) well log analysis (Aristodemou et al, 2005;Maiti et al, 2007;Tiwari, 2009, 2010b), (3) first arrival picking (Murat and Rudman, 1993), (4) earthquake time series modeling (Feng et al, 1997), (5) inversion (Raiche, 1991;Devilee et al, 1999), (6) parameter estimation in geophysics (Macias et al, 2000), (7) prediction of aquifer water level (Coppola et al, 2005;Tsanis et al, 2008), (8) magneto-telluric data inversion (Spichak and Popova, 2000), (9) magnetic interpretations (Bescoby et al, 2006), (10) signal discrimination (Maiti and Tiwari, 2010a), (11) DC resistivity inversion (Qady and Ushijima, 2001;Singh et al, 2010;Maiti et al, 2011). There are, however, several limitations in conventional neural network approaches (Bishop, 1995;Maiti and Tiwari, 2009). One of the main problems is that the network is trained by maximizing a likelihood function of the connection weights or equivalently minimizing an error function in order to obtain the best set of connection weights starting with an initial random set of connection weights.…”
Section: Introductionmentioning
confidence: 98%